다음 방정식을 풀어 라 ...? 2 ^ (4x) -5 (2 ^ (2x-1 / 2)) + 2 = 0

다음 방정식을 풀어 라 ...? 2 ^ (4x) -5 (2 ^ (2x-1 / 2)) + 2 = 0
Anonim

대답:

# x = ln ((25 + -sqrt (609)) / (2sqrt (2))) / (ln4) #

설명:

# 2 ^ (4x) -5 (2 ^ (2x-1 / 2)) + 2 = 0 =

# 2 ^ (2x) ^ 2) -5 * 2 ^ (2x) 색상 (빨강) (xx) 5 * 2 ^ (- 1/2) + 2 = 0 <

2 ^ (2x) + 2 = 0 <=> # (2 ^ 2) ^ 2- (25 / sqrt (2)

이제 2 차 방정식은 쉽게 볼 수 있어야합니다.

대체해야합니다. # 2 ^ (2x) # y로.

# <=> y ^ 2- (25 / (2)) y + 2 = 0 #

# y = (25 / sqrt (2) + - sqrt (625 / 2-2 * 2 * 2)) / 2 #

# y = (25 / sqrt (2) + - sqrt (609/2)) / 2 #

(2x) = y = (25 / sqrt (2) + - sqrt (609/2)) / 2 #

로그 함수:

# 2xln2 = ln ((25 + -sqrt (609)) / (2sqrt (2)))

(25 + -sqrt (609)) / (2sqrt (2))) / (2ln2) #

# x = ln ((25 + -sqrt (609)) / (2sqrt (2))) / (ln4) #